Anaerobic treatment of a metalworking fluid and overcoming the toxic effects on the biodegradation process - Yang, K (2016)
Metalworking fluids (MWFs) are petroleum emulsions employed for metal machining processes as coolants and lubricants. To date, they have been irreplaceable in modern heavy and manufacturing industries, with annual usage exceeding two billion litres worldwide. However, the large amount of MWFs, the highly concentrated complex recalcitrant and toxic petroleum components contained in them continue to cause significant concern in terms of sustainable routes of end-of-life treatment and disposal. Compared with other treatment methods, the anaerobic treatment method has significant advantages, such as the low capital, operating and maintenance costs and energy recovery. This latter factor has the potential benefit of generating bio-energy from waste organic matter whilst aerobic route leads to CO2 emission. However, the bio-toxicity of MWFs is a huge challenge in terms of employing bio-treatment of waste MWFs. In this study, the anaerobic biodegradability of a typical MWF was investigated employing an activated sludge experimental system. Furthermore, the toxic effects of the MWF on the anaerobic ecosystem, particularly on methanogen species, were investigated using bio-molecular analytical methods and a biosensor. In order to overcome its toxicity, the indigenous anaerobic bacteria isolated from spent MWFs were employed in the treatment of the MWF since they were assumed to be acclimated to the conditions. The major findings include: (1) approximately 80% of the MWF (5,000mgCOD/L) was found to be anaerobically biodegradable, with around 35% of the biodegraded COD could be converted to methane; (2) the MWF appeared to be toxic to the anaerobic ecosystem, especially to methanogen species; and (3) however, treatment employing the anaerobic bacteria successfully reduced the toxicity of the MWF and enhanced the methane production in the process.